PENGARUH KUALITAS JASA TERHADAP KEPERCAYAAN DAN KEPUASAN PADA TOURIST INFORMATION CENTRE SURABAYA - Kurnia Maharani Putri; I Wayan Suardana; Ni Putu Eka Mahadewi (Jurnal IPTA (Industri Perjalanan Wisata), 2019)
Tourist Information Centre is one of the important tourism supporting facilities in a tourist destination precisely in the city of Surabaya. The purpose of this study to determine the effect of service quality from the Tourist Information Center to the trust and satisfaction of tourists who visit. This research was conducted at the Tourist Information Center of Surabaya City. Types of data used are qualitative and quantitative data, data collection using questionnaire method, interview and observation. Determination of sample is done by purposive sampling whereas sampling method using representative method of number of indicator multiplied 5 until 10 with get result of 180 tourist. The collected data were analyzed by path analysis method using PLS.The result of the research shows that service quality has significant effect to trust havin gprobability value <0,05, service quality have significant influence to satisfaction with probability value <0,05 and trust have significant effect to satisfaction with probability value <0,05. It states that all hypotheses are accepted. The trust variable proves to be an intervening of 0.6873 which means that variable increasing trust will be a good bridge to the relationship between service quality and satisfaction. The suggestion to increase Tourist Information Center in order to facilitate the access of tourists in obtaining in formation about tourism. And more to place the location to be easily known by tourists.